DEVELOPMENT OF INTEGRATED SCIENCE E-MODULES ON THE MATERIAL INTERACTION OF LIVING THINGS WITH THE ENVIRONMENT USING THE ISPRING SUITE 8 APPLICATION FOR GRADE VII STUDENTS SMP/MTs - vina safitri; Tuti Lestari (Department of Science Education, 2020)
Digital teaching materials are innvovations in the world of education. The rapid development of technology has encouraged various educational institutions to create digital teaching materials. Digital teaching materials can be taken from the internet or other sources in the from of articles, e-books, and e-modules. E-modules is an electronic version of a module designed systematically and interestingly to achieve competence. The reality is that at SMP N 21 Padang students are less motivated to use teaching materials in the form of printed modules. The solution to this problem is to develop electronic module teaching materials. The study aims to reveal the level of validity and practicality of the modules developed. This type of research is Research and Development. The data source is derived from the results of the validity test and practicality test of the instruments used in this study are the interview sheet, validation questionnaire sheet, practicality questionnaire sheet. The results of this study indicate that the integrated natural science e-module of interaction of living things with the environment is very valid with a value of 87.97, and the use of e-modules is very practical according to teachers and students with values of 93.87 and 88.59 respectively.